MEKANISME PEMOTONGAN, PENYETORAN DAN PELAPORAN PPH PASAL 4 AYAT (2) ATAS SEWA TANAH DAN/ATAU BANGUNAN PADA PT. SENTRA AKTIVA INDONESIA. - Silviana Tikasabella, (2023)
Taxes are the biggest source of revenue for the state. Taxes are used for state development and make taxes the largest source of financing. Income tax is one type of tax which is the largest revenue for the state. One of the tax objects of the final Income Tax is land and/or building rental services. The purpose of this study is to find out the mechanism for deducting, depositing and reporting against Income Tax Article 4 Paragraph (2) on the rent of land and buildings at PT. Asset Center. The method used is descriptive analysis method. Based on the research results it is known that PT. Sentra Aktiva Indonesia has complied with Government Regulations in carrying out procedures for withholding, depositing and reporting taxes using a rate of 10% on the Tax Imposition Basis (DPP) of the gross amount of the rental value.